Neurovascular outcome of anterior communicating artery aneurysm in children: a review of the literature and a case report - Emeka Alfred Clement; Rosina Twumwaa Gyamera; Mahjouba Boutarbouch (Egyptian Journal of Neurosurgery)
Abstract There is little information available on clinical presentations, treatment options, and long-term neurovascular consequences of anterior communicating artery (ACoA) aneurysms in children. Although intracranial aneurysms are more common in adults, pediatric cases pose diagnostic and therapeutic challenges due to differences in vascular structure, etiology, and treatment approaches. This study presents a comprehensive review of the literature on ACoA aneurysms in children, highlighting their epidemiology, pathophysiology, clinical manifestations, and treatment modalities, including microsurgical clipping which the patients benefited from. According to our findings, more research is required to contribute to the expanding body of information about pediatric cerebral aneurysms and offering evidence-based management recommendations.